Datasets:
Tasks:
Text Generation
Modalities:
Text
Sub-tasks:
language-modeling
Languages:
English
Size:
100K - 1M
License:
/- | |
Copyright (c) 2022 Wrenna Robson. All rights reserved. | |
Released under Apache 2.0 license as described in the file LICENSE. | |
Authors: Wrenna Robson | |
-/ | |
import analysis.normed_space.basic | |
/-! | |
# Hamming spaces | |
The Hamming metric counts the number of places two members of a (finite) Pi type | |
differ. The Hamming norm is the same as the Hamming metric over additive groups, and | |
counts the number of places a member of a (finite) Pi type differs from zero. | |
This is a useful notion in various applications, but in particular it is relevant | |
in coding theory, in which it is fundamental for defining the minimum distance of a | |
code. | |
## Main definitions | |
* `hamming_dist x y`: the Hamming distance between `x` and `y`, the number of entries which differ. | |
* `hamming_norm x`: the Hamming norm of `x`, the number of non-zero entries. | |
* `hamming β`: a type synonym for `Π i, β i` with `dist` and `norm` provided by the above. | |
* `hamming.to_hamming`, `hamming.of_hamming`: functions for casting between `hamming β` and | |
`Π i, β i`. | |
* `hamming.normed_add_comm_group`: the Hamming norm forms a normed group on `hamming β`. | |
-/ | |
section hamming_dist_norm | |
open finset function | |
variables {α ι : Type*} {β : ι → Type*} [fintype ι] [Π i, decidable_eq (β i)] | |
variables {γ : ι → Type*} [Π i, decidable_eq (γ i)] | |
/-- The Hamming distance function to the naturals. -/ | |
def hamming_dist (x y : Π i, β i) : ℕ := (univ.filter (λ i, x i ≠ y i)).card | |
/-- Corresponds to `dist_self`. -/ | |
@[simp] lemma hamming_dist_self (x : Π i, β i) : hamming_dist x x = 0 := | |
by { rw [hamming_dist, card_eq_zero, filter_eq_empty_iff], exact λ _ _ H, H rfl } | |
/-- Corresponds to `dist_nonneg`. -/ | |
lemma hamming_dist_nonneg {x y : Π i, β i} : 0 ≤ hamming_dist x y := zero_le _ | |
/-- Corresponds to `dist_comm`. -/ | |
lemma hamming_dist_comm (x y : Π i, β i) : hamming_dist x y = hamming_dist y x := | |
by simp_rw [hamming_dist, ne_comm] | |
/-- Corresponds to `dist_triangle`. -/ | |
lemma hamming_dist_triangle (x y z : Π i, β i) : | |
hamming_dist x z ≤ hamming_dist x y + hamming_dist y z := | |
begin | |
classical, simp_rw hamming_dist, refine le_trans (card_mono _) (card_union_le _ _), | |
rw ← filter_or, refine monotone_filter_right _ _, intros i h, | |
by_contra' H, exact h (eq.trans H.1 H.2) | |
end | |
/-- Corresponds to `dist_triangle_left`. -/ | |
lemma hamming_dist_triangle_left (x y z : Π i, β i) : | |
hamming_dist x y ≤ hamming_dist z x + hamming_dist z y := | |
by { rw hamming_dist_comm z, exact hamming_dist_triangle _ _ _ } | |
/-- Corresponds to `dist_triangle_right`. -/ | |
lemma hamming_dist_triangle_right (x y z : Π i, β i) : | |
hamming_dist x y ≤ hamming_dist x z + hamming_dist y z := | |
by { rw hamming_dist_comm y, exact hamming_dist_triangle _ _ _ } | |
/-- Corresponds to `swap_dist`. -/ | |
theorem swap_hamming_dist : swap (@hamming_dist _ β _ _) = hamming_dist := | |
by { funext x y, exact hamming_dist_comm _ _ } | |
/-- Corresponds to `eq_of_dist_eq_zero`. -/ | |
lemma eq_of_hamming_dist_eq_zero {x y : Π i, β i} : hamming_dist x y = 0 → x = y := | |
by simp_rw [ hamming_dist, card_eq_zero, filter_eq_empty_iff, not_not, | |
funext_iff, mem_univ, forall_true_left, imp_self] | |
/-- Corresponds to `dist_eq_zero`. -/ | |
@[simp] lemma hamming_dist_eq_zero {x y : Π i, β i} : hamming_dist x y = 0 ↔ x = y := | |
⟨eq_of_hamming_dist_eq_zero, (λ H, by {rw H, exact hamming_dist_self _})⟩ | |
/-- Corresponds to `zero_eq_dist`. -/ | |
@[simp] lemma hamming_zero_eq_dist {x y : Π i, β i} : 0 = hamming_dist x y ↔ x = y := | |
by rw [eq_comm, hamming_dist_eq_zero] | |
/-- Corresponds to `dist_ne_zero`. -/ | |
lemma hamming_dist_ne_zero {x y : Π i, β i} : hamming_dist x y ≠ 0 ↔ x ≠ y := | |
not_iff_not.mpr hamming_dist_eq_zero | |
/-- Corresponds to `dist_pos`. -/ | |
lemma hamming_dist_pos {x y : Π i, β i} : 0 < hamming_dist x y ↔ x ≠ y := | |
by rw [←hamming_dist_ne_zero, iff_not_comm, not_lt, nat.le_zero_iff] | |
@[simp] lemma hamming_dist_lt_one {x y : Π i, β i} : hamming_dist x y < 1 ↔ x = y := | |
by {rw nat.lt_one_iff, exact hamming_dist_eq_zero} | |
lemma hamming_dist_le_card_fintype {x y : Π i, β i} : | |
hamming_dist x y ≤ fintype.card ι := card_le_univ _ | |
lemma hamming_dist_comp_le_hamming_dist (f : Π i, γ i → β i) {x y : Π i, γ i} : | |
hamming_dist (λ i, f i (x i)) (λ i, f i (y i)) ≤ hamming_dist x y := | |
card_mono (monotone_filter_right _ $ λ i H1 H2, H1 $ congr_arg (f i) H2) | |
lemma hamming_dist_comp (f : Π i, γ i → β i) {x y : Π i, γ i} (hf : Π i, injective (f i)) : | |
hamming_dist (λ i, f i (x i)) (λ i, f i (y i)) = hamming_dist x y := | |
begin | |
refine le_antisymm (hamming_dist_comp_le_hamming_dist _) _, | |
exact card_mono (monotone_filter_right _ $ λ i H1 H2, H1 $ hf i H2) | |
end | |
lemma hamming_dist_smul_le_hamming_dist [Π i, has_smul α (β i)] {k : α} {x y : Π i, β i} : | |
hamming_dist (k • x) (k • y) ≤ hamming_dist x y := | |
hamming_dist_comp_le_hamming_dist $ λ i, (•) k | |
/-- Corresponds to `dist_smul` with the discrete norm on `α`. -/ | |
lemma hamming_dist_smul [Π i, has_smul α (β i)] {k : α} {x y : Π i, β i} | |
(hk : Π i, is_smul_regular (β i) k) : hamming_dist (k • x) (k • y) = hamming_dist x y := | |
hamming_dist_comp (λ i, (•) k) hk | |
section has_zero | |
variables [Π i, has_zero (β i)] [Π i, has_zero (γ i)] | |
/-- The Hamming weight function to the naturals. -/ | |
def hamming_norm (x : Π i, β i) : ℕ := hamming_dist x 0 | |
/-- Corresponds to `dist_zero_right`. -/ | |
lemma hamming_dist_zero_right (x : Π i, β i) : hamming_dist x 0 = hamming_norm x := rfl | |
/-- Corresponds to `dist_zero_left`. -/ | |
lemma hamming_dist_zero_left : hamming_dist (0 : Π i, β i) = hamming_norm := | |
funext $ λ x, by rw [hamming_dist_comm, hamming_dist_zero_right] | |
/-- Corresponds to `norm_nonneg`. -/ | |
lemma hamming_norm_nonneg {x : Π i, β i} : 0 ≤ hamming_norm x := hamming_dist_nonneg | |
/-- Corresponds to `norm_zero`. -/ | |
@[simp] lemma hamming_norm_zero : hamming_norm (0 : Π i, β i) = 0 := hamming_dist_self _ | |
/-- Corresponds to `norm_eq_zero`. -/ | |
@[simp] lemma hamming_norm_eq_zero {x : Π i, β i} : hamming_norm x = 0 ↔ x = 0 := | |
hamming_dist_eq_zero | |
/-- Corresponds to `norm_ne_zero_iff`. -/ | |
lemma hamming_norm_ne_zero_iff {x : Π i, β i} : hamming_norm x ≠ 0 ↔ x ≠ 0 := | |
hamming_dist_ne_zero | |
/-- Corresponds to `norm_pos_iff`. -/ | |
lemma hamming_norm_pos_iff {x : Π i, β i} : 0 < hamming_norm x ↔ x ≠ 0 := hamming_dist_pos | |
@[simp] lemma hamming_norm_lt_one {x : Π i, β i} : hamming_norm x < 1 ↔ x = 0 := hamming_dist_lt_one | |
lemma hamming_norm_le_card_fintype {x : Π i, β i} : hamming_norm x ≤ fintype.card ι := | |
hamming_dist_le_card_fintype | |
lemma hamming_norm_comp_le_hamming_norm (f : Π i, γ i → β i) {x : Π i, γ i} (hf : Π i, f i 0 = 0) : | |
hamming_norm (λ i, f i (x i)) ≤ hamming_norm x := | |
begin | |
refine eq.trans_le _ (hamming_dist_comp_le_hamming_dist f), | |
simp_rw [hamming_norm, pi.zero_def, hf], | |
end | |
lemma hamming_norm_comp (f : Π i, γ i → β i) {x : Π i, γ i} (hf₁ : Π i, injective (f i)) | |
(hf₂ : Π i, f i 0 = 0) : hamming_norm (λ i, f i (x i)) = hamming_norm x := | |
begin | |
simp_rw ← hamming_dist_zero_right, convert hamming_dist_comp f hf₁, | |
simp_rw [pi.zero_apply, hf₂], refl | |
end | |
lemma hamming_norm_smul_le_hamming_norm [has_zero α] [Π i, smul_with_zero α (β i)] {k : α} | |
{x : Π i, β i} : hamming_norm (k • x) ≤ hamming_norm x := | |
hamming_norm_comp_le_hamming_norm (λ i (c : β i), k • c) (λ i, by simp_rw smul_zero') | |
lemma hamming_norm_smul [has_zero α] [Π i, smul_with_zero α (β i)] {k : α} | |
(hk : ∀ i, is_smul_regular (β i) k) (x : Π i, β i) : hamming_norm (k • x) = hamming_norm x := | |
hamming_norm_comp (λ i (c : β i), k • c) hk (λ i, by simp_rw smul_zero') | |
end has_zero | |
/-- Corresponds to `dist_eq_norm`. -/ | |
lemma hamming_dist_eq_hamming_norm [Π i, add_group (β i)] (x y : Π i, β i) : | |
hamming_dist x y = hamming_norm (x - y) := | |
by simp_rw [← hamming_dist_zero_right, hamming_dist, pi.sub_apply, | |
pi.zero_apply, sub_ne_zero] | |
end hamming_dist_norm | |
/-! ### The `hamming` type synonym -/ | |
/-- Type synonym for a Pi type which inherits the usual algebraic instances, but is equipped with | |
the Hamming metric and norm, instead of `pi.normed_add_comm_group` which uses the sup norm. -/ | |
def hamming {ι : Type*} (β : ι → Type*) : Type* := Π i, β i | |
namespace hamming | |
variables {α ι : Type*} {β : ι → Type*} | |
/-! Instances inherited from normal Pi types. -/ | |
instance [Π i, inhabited (β i)] : inhabited (hamming β) := ⟨λ i, default⟩ | |
instance [decidable_eq ι] [fintype ι] [Π i, fintype (β i)] : fintype (hamming β) := pi.fintype | |
instance [inhabited ι] [∀ i, nonempty (β i)] [nontrivial (β default)] : | |
nontrivial (hamming β) := pi.nontrivial | |
instance [fintype ι] [Π i, decidable_eq (β i)] : decidable_eq (hamming β) := | |
fintype.decidable_pi_fintype | |
instance [Π i, has_zero (β i)] : has_zero (hamming β) := pi.has_zero | |
instance [Π i, has_neg (β i)] : has_neg (hamming β) := pi.has_neg | |
instance [Π i, has_add (β i)] : has_add (hamming β) := pi.has_add | |
instance [Π i, has_sub (β i)] : has_sub (hamming β) := pi.has_sub | |
instance [Π i, has_smul α (β i)] : has_smul α (hamming β) := pi.has_smul | |
instance [has_zero α] [Π i, has_zero (β i)] [Π i, smul_with_zero α (β i)] : | |
smul_with_zero α (hamming β) := pi.smul_with_zero _ | |
instance [Π i, add_monoid (β i)] : add_monoid (hamming β) := pi.add_monoid | |
instance [Π i, add_comm_monoid (β i)] : add_comm_monoid (hamming β) := pi.add_comm_monoid | |
instance [Π i, add_comm_group (β i)] : add_comm_group (hamming β) := pi.add_comm_group | |
instance (α) [semiring α] (β : ι → Type*) [Π i, add_comm_monoid (β i)] | |
[Π i, module α (β i)] : module α (hamming β) := pi.module _ _ _ | |
/-! API to/from the type synonym. -/ | |
/-- `to_hamming` is the identity function to the `hamming` of a type. -/ | |
@[pattern] def to_hamming : (Π i, β i) ≃ hamming β := equiv.refl _ | |
/-- `of_hamming` is the identity function from the `hamming` of a type. -/ | |
@[pattern] def of_hamming : hamming β ≃ Π i, β i := equiv.refl _ | |
@[simp] lemma to_hamming_symm_eq : (@to_hamming _ β).symm = of_hamming := rfl | |
@[simp] lemma of_hamming_symm_eq : (@of_hamming _ β).symm = to_hamming := rfl | |
@[simp] lemma to_hamming_of_hamming (x : hamming β) : to_hamming (of_hamming x) = x := rfl | |
@[simp] lemma of_hamming_to_hamming (x : Π i, β i) : of_hamming (to_hamming x) = x := rfl | |
@[simp] lemma to_hamming_inj {x y : Π i, β i} : to_hamming x = to_hamming y ↔ x = y := iff.rfl | |
@[simp] lemma of_hamming_inj {x y : hamming β} : of_hamming x = of_hamming y ↔ x = y := iff.rfl | |
@[simp] lemma to_hamming_zero [Π i, has_zero (β i)] : to_hamming (0 : Π i, β i) = 0 := rfl | |
@[simp] lemma of_hamming_zero [Π i, has_zero (β i)] : of_hamming (0 : hamming β) = 0 := rfl | |
@[simp] lemma to_hamming_neg [Π i, has_neg (β i)] {x : Π i, β i} : | |
to_hamming (-x) = - to_hamming x := rfl | |
@[simp] lemma of_hamming_neg [Π i, has_neg (β i)] {x : hamming β} : | |
of_hamming (-x) = - of_hamming x := rfl | |
@[simp] lemma to_hamming_add [Π i, has_add (β i)] {x y : Π i, β i} : | |
to_hamming (x + y) = to_hamming x + to_hamming y := rfl | |
@[simp] lemma of_hamming_add [Π i, has_add (β i)] {x y : hamming β} : | |
of_hamming (x + y) = of_hamming x + of_hamming y := rfl | |
@[simp] lemma to_hamming_sub [Π i, has_sub (β i)] {x y : Π i, β i} : | |
to_hamming (x - y) = to_hamming x - to_hamming y := rfl | |
@[simp] lemma of_hamming_sub [Π i, has_sub (β i)] {x y : hamming β} : | |
of_hamming (x - y) = of_hamming x - of_hamming y := rfl | |
@[simp] lemma to_hamming_smul [Π i, has_smul α (β i)] {r : α} {x : Π i, β i} : | |
to_hamming (r • x) = r • to_hamming x := rfl | |
@[simp] lemma of_hamming_smul [Π i, has_smul α (β i)] {r : α} {x : hamming β} : | |
of_hamming (r • x) = r • of_hamming x := rfl | |
section | |
/-! Instances equipping `hamming` with `hamming_norm` and `hamming_dist`. -/ | |
variables [fintype ι] [Π i, decidable_eq (β i)] | |
instance : has_dist (hamming β) := ⟨λ x y, hamming_dist (of_hamming x) (of_hamming y)⟩ | |
@[simp, push_cast] lemma dist_eq_hamming_dist (x y : hamming β) : | |
dist x y = hamming_dist (of_hamming x) (of_hamming y) := rfl | |
instance : pseudo_metric_space (hamming β) := | |
{ dist_self := by { push_cast, exact_mod_cast hamming_dist_self }, | |
dist_comm := by { push_cast, exact_mod_cast hamming_dist_comm }, | |
dist_triangle := by { push_cast, exact_mod_cast hamming_dist_triangle }, | |
to_uniform_space := ⊥, | |
uniformity_dist := uniformity_dist_of_mem_uniformity _ _ $ λ s, begin | |
push_cast, | |
split, | |
{ refine λ hs, ⟨1, zero_lt_one, λ _ _ hab, _⟩, | |
rw_mod_cast [hamming_dist_lt_one] at hab, | |
rw [of_hamming_inj, ← mem_id_rel] at hab, | |
exact hs hab }, | |
{ rintros ⟨_, hε, hs⟩ ⟨_, _⟩ hab, | |
rw mem_id_rel at hab, | |
rw hab, | |
refine hs (lt_of_eq_of_lt _ hε), | |
exact_mod_cast hamming_dist_self _ } | |
end, | |
to_bornology := ⟨⊥, bot_le⟩, | |
cobounded_sets := begin | |
ext, | |
push_cast, | |
refine iff_of_true (filter.mem_sets.mpr filter.mem_bot) ⟨fintype.card ι, λ _ _ _ _, _⟩, | |
exact_mod_cast hamming_dist_le_card_fintype | |
end, | |
..hamming.has_dist } | |
@[simp, push_cast] lemma nndist_eq_hamming_dist (x y : hamming β) : | |
nndist x y = hamming_dist (of_hamming x) (of_hamming y) := rfl | |
instance : metric_space (hamming β) := | |
{ eq_of_dist_eq_zero := | |
by { push_cast, exact_mod_cast @eq_of_hamming_dist_eq_zero _ _ _ _ }, | |
..hamming.pseudo_metric_space } | |
instance [Π i, has_zero (β i)] : has_norm (hamming β) := ⟨λ x, hamming_norm (of_hamming x)⟩ | |
@[simp, push_cast] lemma norm_eq_hamming_norm [Π i, has_zero (β i)] (x : hamming β) : | |
∥x∥ = hamming_norm (of_hamming x) := rfl | |
instance [Π i, add_comm_group (β i)] : seminormed_add_comm_group (hamming β) := | |
{ dist_eq := by { push_cast, exact_mod_cast hamming_dist_eq_hamming_norm }, ..pi.add_comm_group } | |
@[simp, push_cast] lemma nnnorm_eq_hamming_norm [Π i, add_comm_group (β i)] (x : hamming β) : | |
∥x∥₊ = hamming_norm (of_hamming x) := rfl | |
instance [Π i, add_comm_group (β i)] : normed_add_comm_group (hamming β) := | |
{ ..hamming.seminormed_add_comm_group } | |
end | |
end hamming | |